2015
DOI: 10.3109/15563650.2015.1022896
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity profile of tolperisone in overdose: Observational poison centre-based study

Abstract: (2015). Acute toxicity profile of tolperisone in overdose: Observational poison centre-based study. Clinical Toxicology, 53 (5) The paper is written in UK English.Running head: Acute toxicity profile of tolperisone in overdose.Word count (excluding references, figure, and abstract): 2075References: 29 Grant or other financial support:The present work was supported entirely by internal resources of the participating study sites. ABSTRACTIntroduction: Tolperisone is a centrally-acting muscle relaxant that acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The toxicity of toperidone hydrochloride, methyl hesperidin, and vitamin B6 has not been reported before. The side effects of tolperisone hydrochloride reported at present is not clear (Ribi et al, 2003; Sporkert et al, 2012; Martos et al, 2015). In animal studies, methyl hesperidin has not been found to have toxic or side effects before (Kawabe et al, 1993).…”
Section: Discussionmentioning
confidence: 81%
“…The toxicity of toperidone hydrochloride, methyl hesperidin, and vitamin B6 has not been reported before. The side effects of tolperisone hydrochloride reported at present is not clear (Ribi et al, 2003; Sporkert et al, 2012; Martos et al, 2015). In animal studies, methyl hesperidin has not been found to have toxic or side effects before (Kawabe et al, 1993).…”
Section: Discussionmentioning
confidence: 81%
“…A common trend seen over the included studies was that the intent behind the pharmaceutical poisoning varied depending on age. Fifteen of the studies reported on pharmaceutical poisoning in children, of which 70.2% were exposed accidently (n = 76,398) [42,49,61,67,75,76,78,82,86,91,92,[94][95][96][97]. Five studies had separated results for adult exposure where 80.9% of exposures were intentional (n = 725) [73,78,94,96,98].…”
Section: Low-middle-income Countries (N = 21)mentioning
confidence: 99%
“…(Figure 2) A common trend seen over the included studies was that the intent behind the pharmaceutical poisoning varied depending on age. Fifteen of the studies reported on pharmaceutical poisoning in children, of which 70.2% were exposed accidently (n=76,398) [38,45,57,63,71,72,74,75,79,83,88,89,[104][105][106]. Five studies had separated results for adult exposure where 80.9% of exposures were intentional (n=725) [69,74,75,98,105].…”
Section: Reason Behind Toxic Exposurementioning
confidence: 99%